2016
DOI: 10.1016/j.jnucmat.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction measurement of residual stresses, dislocation density and texture in Zr-bonded U-10Mo “mini” fuel foils and plates

Abstract: Al clad U-10Mo fuel plates are being considered for conversion of several research reactors from high-enriched to low-enriched U fuel. Neutron diffraction measurements of the textures, residual phase stresses, and dislocation densities in the individual phases of the mini-foils throughout several processing steps and following hot-isostatic pressing to the Al cladding, have been completed. Recovery and recrystallization of the bare U-10Mo fuel foil, as indicated by the dislocation density and texture, are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The lattice parameters of the plasma spray coated samples were 3.492-3.505 Å (standard deviation for the eight measurement results σ = 0.010 Å) for a-axis of γ-U. The parameters are sensitive to residual strain, part of which is derived from thermal contraction difference between the coating and the substrate [2]. The amount of thermal contraction depends on the coating temperature, so the variation of the lattice parameters is due to differences in the heating pattern in the coating process.…”
Section: γ-U Texturementioning
confidence: 99%
See 3 more Smart Citations
“…The lattice parameters of the plasma spray coated samples were 3.492-3.505 Å (standard deviation for the eight measurement results σ = 0.010 Å) for a-axis of γ-U. The parameters are sensitive to residual strain, part of which is derived from thermal contraction difference between the coating and the substrate [2]. The amount of thermal contraction depends on the coating temperature, so the variation of the lattice parameters is due to differences in the heating pattern in the coating process.…”
Section: γ-U Texturementioning
confidence: 99%
“…In the case of steels, the cold rolling texture with reductions around 60% shows ODF intensities of more than 5.0 mrd, which is stronger than that of the recrystallization texture. Brown et al [2] suggested that a U-10Mo sample which was cold-rolled with a 50% reduction and annealed at 650 • C also shows a recrystallization texture. Compared to the experiment in [2], manufacturing processes in this study consisted of a slightly higher cold rolling reduction and higher annealing temperature, which are more preferable conditions for recrystallization.…”
Section: γ-U Texturementioning
confidence: 99%
See 2 more Smart Citations
“…Brown et al researched the residual stress, dislocation density, and texture of U-10Mo alloy on the Spectrometer for Materials Research at Temperature and Stress (SMARTS) at the Los Alamos Neutron Science Center (LANSCE, Los Alamos, NM, USA). They found that the thermal expansion mismatch was the main reason affecting the distribution of residual stress in this material [11]. Using the ENGIN-X strain diffractometer at the Science and Technology Facilities Council's (STFC) laboratory (Swindon, UK), Faisal et al clearly demonstrated the residual stress distribution in Mo-C-based anode layers [12].…”
Section: Introductionmentioning
confidence: 97%